Kajian Kenyamanan Termal pada Bangunan Perpustakaan Regional Kota Kendari - Afri Ahyarky Abidin (Arsitektur Universitas Muhammadiyah Kendari, 2023)
The facility is a container that functions to support all community activities in an area that has been provided by the government. Facilities are religious, be it Health, Education, and also religious. The library is a very important facility for the community. The building aims to provide comfort for users so that later users will feel like lingering in the building. Comfort in the building greatly affects the achievement of the function of the building itself. So that these important facilities can function properly. The existence of library facilities in the city of Kendari can be an advancement in the field of education. Libraries with high comfort can attract visitors so they can linger in the building and can carry out activities in the building as best they can. And with this convenience, it can increase the interest in reading in the local community. Therefore we intend to conduct research related to the comfort that exists in the building.